BRAND FRUNC ID DIGITAL MEDIA CONTENT PLANNING - Naufal, Yogascitra; Adhipermana, Luthfi Diar; Putra, Andika Radya; Simamora, Yohana Agustina Christian; Kaniawati, Nina (TOPLAMA, 2024)
The role of digital content in 2023 is very important due to the shifting role of mass media is gradually being replaced by social media. The content published on social media today is creative digital content that aims to increase the awareness of its audience, one of the brands in the city of Bandung called Frunc Id began planning digital content that will be uploaded on its social media channels. The purpose of this content planning is so that the creative digital content produced can provide benefits, and solutions and entertain its audience. This research uses qualitative research methods with a case study approach. The result of this research is that the Frunc Id brand makes a content plan in the form of a brand essence and campaign deck so that the packaging of the digital content presented is more focused according to the segment and gets optimal results. The form of planning presented in the brand essence is a unique value proposition, and target market based on needs, brand benefits, and brand personality.  The planning presented in the campaign is the campaign objective, key message, media plan, and content matrix.